2016
DOI: 10.11138/gchir/2016.37.3.113
|View full text |Cite
|
Sign up to set email alerts
|

Robotic versus laparoscopic sacrocolpopexy for apical prolapse: a case-control study

Abstract: The apical prolapse has always been considered the most complex of the defects of the pelvic floor, for both the difficulty of the surgical corrective technique and for the high post-surgical recurrence rate. This is a fairly frequent pathological condition. It is estimated that in her life 1/10 women undergoes a hysterectomy and up to 10% of these requiring surgical correction of apical prolapse (1). The standard treatment for surgical management of apical prolapse is abdominal sacrocolpopexy (ASC) (2). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…Studies comparing LS and RSC did not show differences between groups in success outcomes. Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee .…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies comparing LS and RSC did not show differences between groups in success outcomes. Biler et al, in the study about abdominal sacropexy, LS and pectopexy, found no occurrences of de novo apical prolapse at 6 months follow‐up. In studies regarding pectopexy, we found one (2.3%) relapse of apical prolapse after pectopexy reported by Noe after 21.8 months of follow‐up and none in the initial study by Banerjee .…”
Section: Resultsmentioning
confidence: 97%
“…Native tissue repairs have gained popularity following FDA notifications . Since April 16, 2019, there have been no FDA‐approved surgical mesh products for transvaginal repair marketed for use in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These surgical procedures should to be performed by a surgical team experienced in general, gynaecological, adrenal and urological laparoscopic surgery also in urgency setting because we well know the possible intraoperative complications of this kind of surgery as bowel, bladder, ureteric and vascular injuries (29)(30)(31)(32)(33)(34)(35).…”
Section: © C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 99%